Production flexibility of small run-of-river power plants: KWGO smart-storage case study. Issue 1 (June 2021) - Münch-Alligné, C; Decaix, J; Gaspoz, A; Hasmatuchi, V; Dreyer, M; Nicolet, C; Alimirzazadeh, S; Zordan, J; Manso, P; Crettenand, S
Abstract: In the framework of the new Swiss feed-in-tariff system for Small Hydropower Plants (SHP), the aim of the SmallFLEX project, led by HES-SO Valais and performed in collaboration with EPFL, WSL, EAWAG, PVE and FMV, is to show how SHP can provide winter peak energy and ancillary services, whilst remaining eco-compatible. The pilot and demonstrator site selected is the new SHP of Gletsch-Oberwald (KWGO) owned by FMV and commissioned end of 2017. This run-of-river power plant is equipped with two six-jets Pelton turbine units featuring a maximum power of 7.5 MW each while the average annual power is lower than 5 MW, with a maximum of production during the summer. The capacity of infrastructure, equipment, and other adaptation measures to produce in a flexible way is being assessed while measuring the impact of this new operation on the environment, production and revenues. The paper focuses on the two experimental campaigns and the numerical simulations carried out to assess the flexibility of the power plant by means of smart use of existing infrastructure as additional storage volumes: the settling basin, the forebay and the upper part of the headrace tunnel.